2003
DOI: 10.3354/meps251169
|View full text |Cite
|
Sign up to set email alerts
|

Strontium:calcium ratios in statoliths of Japanese common squid Todarodes pacificus (Cephalopoda: Ommastrephidae) as indicators of migratory behavior

Abstract: Ontogenetic variation in the strontium:calcium (Sr:Ca) ratios was measured in statoliths of the Japanese common squid Todarodes pacificus. Two different geographical groups of T. pacificus inhabit the Sea of Japan; these groups are separated by the Subarctic Front during the summer. Element ratios were measured with a wavelength-dispersive spectrometer for 11 individuals from a cold-water subarctic region, which harbors large squid (Subarctic Group), for 12 individuals from a warm-water region, which harbors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 14 publications
4
38
0
Order By: Relevance
“…Inspired by an inverse relationship between Sr/Ca and temperature in scleractinian corals (Beck et al 1992), several studies have attempted to use Sr/Ca ratios in statoliths as a temperature proxy (e.g. Rodhouse et al 1994, Ikeda et al 2003. Arkhipkin et al (2004) showed a good relationship between Sr/Ca and ambient temperature in statoliths of the Patagonian longfin squid Loligo gahi collected in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by an inverse relationship between Sr/Ca and temperature in scleractinian corals (Beck et al 1992), several studies have attempted to use Sr/Ca ratios in statoliths as a temperature proxy (e.g. Rodhouse et al 1994, Ikeda et al 2003. Arkhipkin et al (2004) showed a good relationship between Sr/Ca and ambient temperature in statoliths of the Patagonian longfin squid Loligo gahi collected in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al 1996) and gastropods (Zacherl et al 2003). For cephalopod statoliths, however, environmental influences have been proposed on the basis of field studies only (Ikeda et al 1996a(Ikeda et al , 2003Yatsu et al 1998). The only study so far that analysed statoliths from reared cephalopods found considerable variations in the Sr/Ca ratio in spite of constant conditions during rearing (Ikeda et al 2002a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Durholtz et al 1997;Lipinski et al 1997;Ikeda et al 2002a, b;Bettencourt and Guerra 2000). Chemical signatures of statoliths have been used as a tool to determine environmental life-histories of the neon flying squid Ommastrephes bartramii (Yatsu et al 1998) and the Japanese common squid Todarodes pacificus (Ikeda et al 2003) as well as to distinguish stocks of the Patagonian longfin squid Loligo gahi (Arkhipkin et al 2004), yet the method remains largely unverified. It is not documented whether the Sr/Ca ratio or any other trace element signature is primarily related to ambient temperature or whether it is simultaneously influenced by salinity or other factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lea & Spero 1994, Brown & Luoma 1995, Shen et al 1996, Alibert & McCulloch 1997, Rosenthal et al 1997, Tzeng et al 1997, Secor et al 2001, Ikeda et al 2003, Zacherl et al 2003). Environmental histories commonly described include water temperature (Alibert & McCulloch 1997), salinity (Kafemann et al 2000) and ambient elemental concentrations (Secor et al 2001), all of which can reconstruct past climatic conditions.…”
Section: Introductionmentioning
confidence: 99%